Ceramides regulate defense response by binding to RbohD in Arabidopsis - Li, Jian; Yin, Jian; Wu, Jian‐Xin; Wang, Ling‐Yan; Liu, Yu; Huang, Li‐Qun; Wang, Rui‐Hua; Yao, Nan (The Plant journal : for cell and molecular biology, 2022)
SUMMARY Sphingolipids, a class of bioactive lipids, play a critical role in signal transduction. Ceramides, which are central components of sphingolipid metabolism, are involved in plant development and defense. However, the mechanistic link between ceramides and downstream signaling remains unclear. Here, the mutation of alkaline ceramidase in a ceramide kinase mutant acd5 resulted in spontaneous programmed cell death early in development and was accompanied by ceramide accumulation, while other types of sphingolipids, such as long chain base, glucosylceramide, and glycosyl inositol phosphorylceramide, remained at the same level as the wild‐type plants. Analysis of the transcriptome indicated that genes related to the salicylic acid (SA) pathway and oxidative stress pathway were induced dramatically in acer acd5 plants. Comparison of the level of reactive oxygen species (ROS), SA, and ceramides in the wild‐type and acer acd5 plants at different developmental stages indicated that the acer acd5 mutant exhibited constitutive activation of SA and ROS signaling, which occurred simultaneously with the alteration of ceramides. Overexpressing NahG in the acer acd5 mutant could completely suppress its cell death and ceramide accumulation, while benzo‐(1,2,3)‐thiadiazole‐7‐carbothioc acid S‐methyl ester treatment restored its phenotype again. Moreover, we found that the plasma membrane of acer acd5 mutant was the main site of ROS production. Ceramides accumulated in the plasma membrane of acer acd5, directly binding and activating the NADPH oxidase RbohD and promoting hydrogen peroxide generation and SA‐ or defense‐related gene activation. Our data illustrated that ceramides play an essential role in plant defense. Significance Statement A growing body of evidence has recently shown that sphingolipids have been implicated in plant development and response to abiotic and biotic stresses, but the molecular mechanisms associated with sphingolipids and defense regulators remain poorly understood. In this report, using ceramide kinase mutant combined with alkaline ceramidase mutant, we report that ceramide accumulation in the plasma membrane modulates reactive oxygen species signaling through RbohD. The identification of RbohD as a direct target of ceramides provides mechanistic insights for better understanding the link between ceramides and reactive oxygen species in the response to environmental stress.